Assessment and treatment of problem behavior maintained by escape from attention. (26th October 2021) - Cengher, Mirela; O'Connor, Julia T.; Strohmeier, Craig W.
Abstract: This study describes the assessment and treatment of problem behavior for two participants whose functional analysis results identified escape from attention as the function of problem behavior. Treatment involved functional communication training to teach an appropriate alternative behavior that produced escape from attention. Additionally, in both cases, we expanded treatments by using graduated exposure to attention to facilitate increases in social interaction while maintaining low levels of problem behavior. We discuss findings as they relate to (a) functional analysis procedures to identify escape from attention as a function for problem behavior, (b) treatment strategies to reduce problem behavior, and (c) treatment strategies aimed at decreasing escape from, and avoidance of, social interaction for individuals who demonstrate this problem behavior function.